1989
DOI: 10.1056/nejm198904133201504
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Nonoperative Treatment for Perforated Peptic Ulcer

Abstract: To determine whether surgery could be avoided in some patients with perforated peptic ulcer, we conducted a prospective randomized trial comparing the outcome of nonoperative treatment with that of emergency surgery in patients with a clinical diagnosis of perforated peptic ulcer. Of the 83 patients entered in the study over a 13-month period, 40 were randomly assigned to conservative treatment, which consisted of resuscitation with intravenous fluids, institution of nasogastric suction, and intravenous admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
146
2
24

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(178 citation statements)
references
References 22 publications
5
146
2
24
Order By: Relevance
“…Crofts et al [148] reported patients below 70 years old were significantly less likely to transfer to surgical therapy than older patients. Many studies reported that age of indication for conservative therapy was less than 70 years.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Crofts et al [148] reported patients below 70 years old were significantly less likely to transfer to surgical therapy than older patients. Many studies reported that age of indication for conservative therapy was less than 70 years.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Comment: Even when surgery is not indicated based on the above statements, follow-up CT is needed for patient observation [148]. If the patient's state is not improved at follow-up, the surgery is indicated.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A fibrin clot appears quickly on and around the perforation. This is the initiation of definitive closure of perforation with the help of adhesions between perforated ulcer and adjacent organs [12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In the Exeter series, 33% of those over 70s had perforation for longer than 24 hours. Conservative treatment is not advised with a history longer than 12 hours [24] . In our study 50% of the patients presented within first 24 hours and another 41% of patients presented within 24-72 hours of onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation